A influência da certificação ambiental AQUA-HQE no processo de projeto: estudo de caso em edifício residencial em Maceió, AL - Accioly, Luísa Fireman Patury (2017)
Given the great increase in environmental impacts generated by construction in the world, there is a growing demand for the implementation of more sustainable methods in the production of the built environment. About performance improvements and building management system, environmental certifications have been adopted as guiding projects. Among the certifications used in Brazil, the AQUA-HQE Process hás been highlighting in the residential sector, interfering in the process of architectural design and complementary. In order to collaborate with this discussion, this research intends to contribute to the understanding of the dynamics of the design of buildings that seek to follow sustainability principles proposed by the certification. The objective of this work is to identify and analyze possible influences in the design process of a residential building to the AQUA-HQE Process certification. For that, a bibliographical review was made focusing on the theme described above, to form a theoretical framework that supports the reflections presented in this work. In order to know a practical application of AQUA-HQE environmental certification, a case study of the Double building, the first residential building certified in the Pre-project and Project stages, located in the city of Maceio, Alagoas. The process of certification of this building was closely observed by the author, in order to know the environmental profile traced to the building through projects, memorials, documents, minutes of meetings and technical dossiers. Guided interviews were also conducted through questionnaire with the professionals involved in the implementation of the AQUA-HQE Process, in order to understand their opinions and experience in participating in the process of this project. Thematic discussions of the results were performed, relating the content of the respondents' responses to the proposed project solutions. The conclusions show that AQUA-HQE directly influenced the entire building design process, generating significant changes both in the dynamics and relationships between designers, as well as in design strategies and solutions.